Recommendation on Company Strategy Formulation to Withstand Early Dicline in Performance of Solid Arkon Indonesia, PT - Narendra, Adi Pradipta; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2013)
Inspired by progressive development architecture industry, PT. Solid Arkon Indonesia or shortened to Solidarkonindo was established, an architectural consulting firm that also offer related field services in attempt to provide a comprehensive service. As a service company, client satisfaction is the main thing that always maintained by providing a characterized, comprehensive, and environmentally oriented design services. However, as time goes the company is experiencing a significant decline in performance, not long after its growing phase since it was first established in September 2011 ago. It is also marked by uncertainty direction of company which had previously been formulated, thus become an obstacle in continuing business sustainability. As a means to analyze the issue encountered, research methodology that used is similar with corporate strategic audit, which encompass the examination and evaluate current firm situation from gathered primary and secondary data as well as literature references. Furthermore, an environment scanning are conduct to analyze internal and external performance to define root causes, which is become guidance in generating most appropriate recommendation of business solution for the firm. Last, provide explanation of way to implement recommended strategy and further recommendation to provide comprehensive implementation guidance. Through several research that has been done, the performance decline which firm experience are caused by prior failure in assessing firm’s internal capabilities compared to its industry environment. This situation, lead to further problems that affect internal management decision in setting corporate and business strategy in deal with growing environment challenges. In order to survive in the industry, several solutions are needed which cover improvement and evaluation of strategic alternatives to generate best alternatives for the firm. The generated solutions based on research objectives, conclude that the firm required an appropriate corporate directional of retrenchment – turnaround strategy, to improve firm’s current condition. An improvement on corporate directional strategy is necessary in the first place because it decide the direction of the firm. Furthermore, a recommended business strategy of focus differentiation provided to set the firm compete in the right market, as well as strategic initiative of grand strategy roadmap that provided as comprehensive guidance in moving to each stages of strategies in the future.Keyword: Architectural consultant services, corporate directional strategy, business strategy, grand strategy roadmap